1994
DOI: 10.1016/s0733-8619(18)30111-7
|View full text |Cite
|
Sign up to set email alerts
|

Reflex Seizures

Abstract: Reflex seizures are best defined as a collective of different seizure types distinguished by their ability to be precipitated by a specific stimulus. This article reviews established reflex syndromes, including data gleaned from the application of intensive monitoring. Animal models are also discussed. The majority of stimulus-sensitive seizures occur in the context of well established, generalized, or localization-related epilepsy syndromes. The study of these phenomena offers insight into sensory and cogniti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
32
0

Year Published

1995
1995
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 91 publications
2
32
0
Order By: Relevance
“…HWE is usually seen in children and various studies have evaluated the seizure onset age. The mean seizure onset age was 13.4 years in the largest series in the literature, but it can be as low as 4.7 years (14,15). We found that the first seizures developed at a mean age of 3.6 years in our patients.…”
Section: Discussionmentioning
confidence: 47%
“…HWE is usually seen in children and various studies have evaluated the seizure onset age. The mean seizure onset age was 13.4 years in the largest series in the literature, but it can be as low as 4.7 years (14,15). We found that the first seizures developed at a mean age of 3.6 years in our patients.…”
Section: Discussionmentioning
confidence: 47%
“…The usual etiologies are genetic or acquired in nature [1]. Focal brain lesions or occult focal cortical dysplasias can evoke reflex seizures.…”
Section: Discussionmentioning
confidence: 99%
“…The stimulus can be simple (flash of light) or more complex like reading, writing, doing arithmetic, or even thinking about specific topics [1]. Seizures occurring during micturition are rare and were first reported in 1964 by Zivin et al [2] and subsequently by few other authors [3][4][5][6][7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…In reflex epilepsy, seizures can be provoked habitually by an external stimulus or, less commonly, internal mental processes. 11,12 Seizures are induced by activation of primary sensory cortices, such as the primary auditory, visual, or somatosensory cortices, as well as of parietal lobe association cortex. 11,12 Reflex partial seizures triggered by tactile or proprioceptive stimuli may develop in lesional epilepsies related to structural brain abnormalities, which are absent in Rett syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…11,12 Seizures are induced by activation of primary sensory cortices, such as the primary auditory, visual, or somatosensory cortices, as well as of parietal lobe association cortex. 11,12 Reflex partial seizures triggered by tactile or proprioceptive stimuli may develop in lesional epilepsies related to structural brain abnormalities, which are absent in Rett syndrome. However, in reflex seizures, the external stimulus is mainly responsible for the onset of epileptic activity but the epileptic activity tends to generalize and its removal does not instantly coincide with disappearance of both epileptiform and motor activity.…”
Section: Discussionmentioning
confidence: 99%